1996
DOI: 10.1080/02640419608727718
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exercise analgesia: Replication and extension

Abstract: This study was designed to investigate whether post-exercise analgesia occurs following an ad lib exercise routine. All of the 17 male participants exercised on a regular basis. In an exercise setting (student gymnasium) they participated in 20 min of self-selected exercise, while in the neutral setting (laboratory) they rested quietly for 20 min. Pain was induced via the gross pressure device. Pain threshold and pain tolerance were measured twice, with an interval of 20 min, in both the exercise and the neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 10 publications
5
19
2
1
Order By: Relevance
“…*P < 0.05 Ac vs Co and + P < 0.05 Ac + Nx vs Ac (one-way ANOVA followed by Bonferroni's test). studies conducted on humans have reported analgesia after resistance exercise, but the subjects had previous resistance exercise experience (9,10). In the present study, however, the resistance exercise protocols involving trained rats (Tr, Tr-Ac) did not produce antinociception.…”
Section: Discussioncontrasting
confidence: 74%
“…*P < 0.05 Ac vs Co and + P < 0.05 Ac + Nx vs Ac (one-way ANOVA followed by Bonferroni's test). studies conducted on humans have reported analgesia after resistance exercise, but the subjects had previous resistance exercise experience (9,10). In the present study, however, the resistance exercise protocols involving trained rats (Tr, Tr-Ac) did not produce antinociception.…”
Section: Discussioncontrasting
confidence: 74%
“…Investigators, for example, have reported elevations in pain tolerances, elevations in pain thresholds, and lower pain ratings after moderate to high intensity resistance exercise. 1,11 A small amount of research has examined the impact of isometric exercise (eg, static muscular contraction) on pain sensitivity, but the results from these studies are equivocal. Several studies have indicated that hypoalgesia did not occur during isometric exercise in healthy adults or in women with fibromyalgia.…”
mentioning
confidence: 99%
“…Improved sleep, enhanced mood, relaxation, reduction in anxiety and general well-being following regular exercise also can alter pain sensitivity positively in same way. After a single exercise session pain tolerance increases significantly [58,88].…”
Section: Benefits Of Exercise In Chronic Musculoskeletal Painmentioning
confidence: 99%